Case Report: A case of hepatic encephalopathy secondary to a spontaneous splenorenal shunt - An, Yulong; Deng, Chao; Wen, Chong; Liu, Jinli; Zhu, Yongqiang; Chen, Kai; Luo, Hao (Frontiers in Surgery, 2026)
This report presents a case of hepatic encephalopathy (HE) induced by a spontaneous splenorenal shunt (SSRS). A 73-year-old male patient was admitted to our medical facility due to loss of consciousness. Laboratory analyses revealed elevated blood ammonia levels and varying degrees of reduction in erythrocyte, leucocyte, and platelet levels. Portal vein imaging utilizing 320-slice CT demonstrated enlargement of the portal and splenic veins, splenomegaly, multiple varicose veins at the splenic hilum, and local protrusion of the left renal vein. An initial diagnosis of HE with SSRS and hypersplenism was established. A multi-disciplinary treatment approach was implemented, incorporating a patient–doctor collaborative decision-making model. Two treatment options were presented to the patient, who opted for surgical intervention over interventional treatment. Subsequently, a combined splenectomy and splenorenal shunt vessel ligation procedure was performed. Postoperatively, the patient's condition exhibited significant improvement compared to his pre-operative state, with no recurrence of HE observed. This article reports a case of recurrent hepatic encephalopathy and severe hypersplenism related to SSRS, which was successfully treated by combined splenectomy and vascular disconnection.